Mantle - Ozima, Minoru; Podosek, Frank A. (Noble Gas Geochemistry, 2001)
IntroductionTheir chemical inertness and low abundance make noble gases a unique geochemical tracer, and their application to the study of mantle geochemistry, differentiation, and volatile separation is one of the major successful developments in recent earth science research. Some noble gas isotopic compositions are quite different between the crust and the mantle, and some of these, such as 40Ar/36Ar and 129Xe/130Xe, involve radiogenic isotopes and thus undergo predictable variations in time. Noble gases thus not only provide information on mantle processes and their spatial variations but also provide chronological constraints. In applying noble gases to the study of mantle geochemistry and dynamics, the subject of this chapter, we must first appraise the noble gas state of the mantle and how it differs from the atmosphere. Despite much recent progress, this issue is not yet settled, and some difficulties should be kept in mind during the following discussion. One difficulty is evaluating how representative of the mantle as a whole the various mantle-derived samples actually are. A second difficulty is that noble gases in mantle samples frequently occur in such low concentrations that there can be technical problems in their analysis. A problem corollary to low abundances is that it is not always easy to distinguish true mantle gases from potential atmospheric contamination.To obtain information on the noble gas state in the mantle, it is necessary to analyze mantle-derived materials that have trapped mantle noble gases.